Photoanodic oxidation of InP in acid solution and its surface chemistry: On the interplay of photons, protons and hydrodynamics. (10th November 2020) - van Dorp, Dennis H.; Vanheusden, Genis; Paulussen, Kris; Hassan, Ibrahim; Van Wonterghem, Simon; Abrenica, Graniel H.; Dara, Praveen; Meersschaut, Johan; Conard, Thierry; Holsteyns, Frank; Kelly, John J.
Abstract: Factors determining etching and passivation of n-type InP in H2 SO4 and HCl solution and the corresponding surface chemistry are considered. Passivation is favoured by higher light intensity and lower proton and Cl − ion concentration. Ex-situ surface analysis shows the passive (bi)layer to consist mainly of oxide-based In 3+ and P 5+ components: InPO4 and In(PO3 )3 . Hydrodynamics is found to play a decisive and surprizing role in determining the kinetics of the surface reactions. Oxygen-bridge formation between surface In and P atoms, as a result of deprotonation of a P-OH reaction intermediate, is considered to be important in determining competition between the two reaction paths: etching and passivation. These results are compared with markedly contrasting results for n-type GaAs under similar experimental conditions.